THE EFFECT OF POSITIVE EMOTIONAL REGULATION TOWARDS HAPPINESS LEVEL IN MENOPAUSAL WOMEN - Juwita, Linda; Sari, Ni Putu Wulan Purnama (Nurse and Holistic Care, 2021)
Background: Menopausal women experience various physical changes leading to psychological problems, such as anxiety, and may cause negative emotions. Regulating positive emotions in menopausal women may increase the happiness level in this population. Objective: This study aims to analyze the effect of positive emotional regulation towards the happiness level in menopausal women Methods: This analytic observational study utilized cross sectional design. The population was all female elders living in community under the supervision of Kenjeran Public Health Center, and the sampel was menopausal women. The independent variable was positive emotional regulation, while the dependent variable was the  happiness level. Valid and reliable questionnaires were used in data collection. Linear regression test was used in data analysis. Results: All respondents (100%) had good positive emotions, and most respondents (59.5%) had a high level of happiness. Linear regression test showed that positive emotional regulation affected the happiness level significantly in menopausal women (p<0.05). Conclusions:  Positive emotions affect the happiness level ini menopausal women.